Acarbose for Postprandial Hypotension With Glucose Metabolism Disorders: A Systematic Review and Meta-Analysis - Wang, Biqing; Zhao, Junnan; Zhan, Qiuxiao; Wang, Rongyanqi; Liu, Birong; Zhou, Yan; Xu, Fengqin (Frontiers in Cardiovascular Medicine, 2021)
Background: Postprandial hypotension (PPH) is an independent predictive factor of all-cause mortality in older people. Drug management has not achieved a satisfactory effect yet. In recent years, many studies have found that acarbose may be effective in the treatment of PPH with glucose metabolism disorders. Objective: To assess the efficacy and safety of acarbose on PPH with glucose metabolism disorders. Methods: PubMed (MEDLINE), Cochrane, EMBASE, Web of Science, Clinical Trials, and relevant Chinese databases were searched from inception to October 1, 2020. Randomized controlled studies of acarbose in the treatment of PPH with glucose metabolism disorders were included. Review Manager 5.3 software was used for quality evaluation and meta-analysis. GRADEpro GDT software was used to GRADE the evidence for the research objectives. Results: A total of 4 randomized controlled studies including 202 participants were identified after screening. The meta-analysis showed that acarbose significantly attenuated the decrease in postprandial systolic blood pressure [weighted mean difference (MD): −9.84, 95% CI: −13.34 to −6.33], diastolic blood pressure (MD: −6.86, 95% CI: −12.89 to −0.83), and mean arterial pressure (MD: −8.10, 95% CI: −12.40 to −3.49) compared with the control group. One study reported a case of adverse reactions that included mild abdominal distension in the acarbose group (4.8%, 1/21). No adverse reactions were reported in the other three studies. Conclusion: Acarbose may attenuate the decrease in postprandial blood pressure and avoid the occurrence of PPH in patients with PPH and abnormal glucose metabolism disorders. More clinical trials are needed to make a clear conclusion. Registration: PROSPERO CRD42020171335.